Onium System for Separation, Preconcentration and Spectrophotometric Determination of Co (II), Via Cloud Point Extraction Methodology - Faris H. Hayder (Journal of Global Pharma Technology, 2018)
According to the Onium system with application of Cloud point extraction (CPE) methodology coupled with spectroscopic method study the separation and the determination of Cobalt(II), with limitation the optimum condition for higher extraction efficiency of Cobalt(II), by using (N-benzoyl-L-arginine ethyl ester hydrochloride)(N-BAEH) and non-ionic Surfactant (1% Triton X–100). Study appears the extracted species giving maximum absorbance at 294 nm, and these methods for separation need 0.8 M HCl in 10 mL aqueous solution. Contain 100 µg of Cobalt (II), as well as need heating at 85 °C for 15 minutes, in the presence of 0.5 mL of Surfactant in aqueous solution.Keywords: Cobalt(II), Cloud Point Extraction, Onium extraction, Halow complex, perconcentration.